Peran Pelacak Find My Device untuk Memperkuat Pertahanan Negara: Materi Pembelajaran pada Pelatihan Keamanan Siber - Charla Susanti; R. Okta Kurniawan (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2026)
Find My Device (FMD) tracker is a technology that can be used to track lost or hacked electronic devices and has great potential in supporting national defense. In the field of national defense, the use of this kind of tracking system can strengthen the country's cyber security and infrastructure, especially in the context of strengthening cyber security and cyber human resource development. This research aims to explore how tracking systems such as FMD can be utilized in developing Cyber ​​Human Resources, to support national defense in an increasingly complex digital era. cyber ​​human resources development is to equip cyber professionals with practical skills in mitigating risks related to lost or hacked devices, as well as increasing the country's capabilities in protecting sensitive data from the threat of hybrid warfare. Using descriptive-analytical research methods based on literature studies and systems analysis, this research examines how tracking technology can help identify and mitigate threats in cyberspace, as well as increase the country's cyber preparedness and resilience. The research results show that, through training and implementing tracking technology, human resources involved in cyber security can hone skills in managing devices and data to strengthen national defense. Utilization of this technology also has the potential to speed up responses to cyber incidents, provide transparency in asset monitoring, and improve coordination between agencies related to national defense. Therefore, human resource education and training using a digital tracking system is important to increase the effectiveness of national cyber defense.